THE FALACY OF PARADOX: AN ANALYSIS OF BINOMIAL RISK-RETURN IN THE BRAZILIAN CAPITAL MARKET - Marques, Vagner Antônio; Costa, Bethânia Mara Lima Família; Lopes, Mariana Borges; Ramos, Sarah Waichert (Advances in Scientific and Applied Accounting, 2021)
Purpose:Theaimofthisstudywastoanalyzethe existence of Bowman’sParadox(PB)intheBraziliancompanieslistedinBrazil,Bolsa,Balcão(B3). Method:Thedescriptivestudy,usingarchivaldata and withquantitativeapproach,analyzedquarterlydatafrom the period2008-2018of292companieslistedinB3andatotalof9,387firmobservations/year. Results: Ours evidence reinforced the hypothesis of positive association between risk and return, both for market proxies and for accounting data. However, it was found that economic and/or normative uncertainties can impair the predictability of returns, resulting in a negative spurious relationship between risk and return. Implications/Contributions: The results reinforce the assumptions of modern finance theory, especially the idea of positive association between risk and return. Contribute to the debate in the management of the investment portfolio in the Brazilian context, including accounting data. The evidence has implications for investors, especially non-institutional and other economic agents who seek to understand the relevant variables in risk investment decision-making.